2016
DOI: 10.1016/j.homp.2015.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Impact of homeopathic remedies on the expression of lineage differentiation genes: an in vitro approach using embryonic stem cells

Abstract: Our study for the first time has shown the feasibility of using ES cells in the developmental toxicity testing of remedies. The results suggest that they are not associated with developmental toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The Indian group used a range of methods including PCR but with the objective of demonstrating safety in pregnancy. 2 They found no significant difference in gene expression between Nux vomica 30c and Sepia officinalis 30c compared to solvent in mouse embryonic stem cells. They conclude that this supports their safety in pregnancy.…”
Section: Pcrmentioning
confidence: 93%
“…The Indian group used a range of methods including PCR but with the objective of demonstrating safety in pregnancy. 2 They found no significant difference in gene expression between Nux vomica 30c and Sepia officinalis 30c compared to solvent in mouse embryonic stem cells. They conclude that this supports their safety in pregnancy.…”
Section: Pcrmentioning
confidence: 93%
“…They found that Sepia, and also Nux vomica, led to modulations in the expression of certain lineage-specific genes, but these differences were not significant with respect to their solvent controls. 75 Several randomized controlled trials, clinical observational studies and case reports have indicated the most important HMs that seem to improve menopausal complaints. The HMM fully describes their most characteristic symptoms.…”
Section: Role Of Dopamine In the Pathophysiology Of Depressionmentioning
confidence: 99%
“…She becomes depressed and indifferent toward anything; only wants to be alone, losing enthusiasm toward life; is irritable and easily offended; expresses great sadness with much weeping, especially when telling her symptoms; feels sluggish and dull, both physically and mentally; has lack of vital heat during chronic diseases; experiences hot flashes, with weakness and perspiration, during menopause; has sensitivity to cold air; faints easily from extremes of temperature or getting wet; and has a bearing-down sensation and constipation. [75][76][77][78] Besides the mental symptoms previously described, it is noticeable that the HMM also describes skin features in Sepia officinalis such as yellowness of face and conjunctiva, yellow spots on the chest, brown saddle over upper parts of cheeks and nose, herpetic eruptions, and lentigo. 63 The Sepia officinalis ink gland is involved in the unique defense mechanism of this cephalopod.…”
Section: Sepia Officinalismentioning
confidence: 99%
See 1 more Smart Citation
“…17 The working concentration for each potency of the drug was 5 μL/mL for all the in vitro studies and was based on our previous published reports. 18,19 Cisplatin was used as positive control at the specified concentration mentioned for each cell line: 1.5 μM (MCF 7) and 1.83 μM (MDA-MB-468). The concentrations of cisplatin used in our study for the specific cell type were based on crystal violet viability assay.…”
Section: Homeopathic Medicinesmentioning
confidence: 99%